THE MACHIAVELLIAN CONCEPT OF CIVIC VIRTUES - MATEI OANA (Societate şi Politică, 2011)
The Machiavellian moment seems to be more andmore influent in the context of the 20th and 21st century. Machiavelli’s legacy,once associated with an immoral way of thinking, is, nowadays, more and moreinterpreted and appreciated. This paper tries to argue that Machiavelli createda new concept of virtues, civic virtues, and this concept is not completelyopposed to the traditional Greek concept of virtue, in fact, virtù and arete aretwo concepts with common origins.